2020
DOI: 10.1002/pol.20200130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular structure of curing agents on cyclic creep in highly cross‐linked epoxy polymers

Abstract: Ratcheting behavior of highly–cross‐linked epoxy polymers was investigated considering the effect of molecular structure of curing agents by molecular dynamics simulations. Cyclic loading–unloading simulations at two different frequencies were conducted using atomistic models for epoxies cured by aliphatic and aromatic curing agents, triethylenetetramine (TETA) and diethyltoluenediamine (DETDA), respectively. Different ratcheting strain evolutions, dihedral angle stress accumulations, and stiffness variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
2
11
1
Order By: Relevance
“…From Figure 5 , the yield strength of the resulting epoxy resin model is 206.64 MPA, and the corresponding strain is 0.052. It should be pointed out that the yield strength 206.64 MPa of epoxy resin simulated here is slightly lower than the 264.26 MPa reported in previous studies, which may be due to the fact that the cross-linking degree of the model established using the method of representative monomer in this paper is slightly lower than that of the previously reported model (81.3%) [ 16 ]. At the same time, through postprocessing to fit the points obtained in the linear stage of the stress-strain curve in the tensile process, we found that the Young’s modulus of the epoxy resin system was 4.390 ± 0.251 GPa, with the final fitting degree R 2 equaling 0.98.…”
Section: Resultscontrasting
confidence: 81%
See 1 more Smart Citation
“…From Figure 5 , the yield strength of the resulting epoxy resin model is 206.64 MPA, and the corresponding strain is 0.052. It should be pointed out that the yield strength 206.64 MPa of epoxy resin simulated here is slightly lower than the 264.26 MPa reported in previous studies, which may be due to the fact that the cross-linking degree of the model established using the method of representative monomer in this paper is slightly lower than that of the previously reported model (81.3%) [ 16 ]. At the same time, through postprocessing to fit the points obtained in the linear stage of the stress-strain curve in the tensile process, we found that the Young’s modulus of the epoxy resin system was 4.390 ± 0.251 GPa, with the final fitting degree R 2 equaling 0.98.…”
Section: Resultscontrasting
confidence: 81%
“…By finding the correlation between the steady-state creep rate and steady-state void nucleation rate, they considered that secondary creep is heavily driven by void nucleation, while tertiary creep is driven by void growth and coalescence. Hyungbum Park et al [ 16 ] conducted the cyclic loading–unloading simulations at two different frequencies using atomistic models for epoxies cured by aliphatic and aromatic curing agents, triethylenetetramine (TETA) and diethyltoluenediamine (DETDA), respectively. They studied the structure and found that irreversible dihedral angle transitions near the benzene ring of the curing agent DETDA were responsible for low ratcheting resistance and stiffness degradation during the cyclic creep deformations.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1a-d show the chemical structures of diglycidyl ether of bisphenol F (DGEBF), triglycidyl p-aminophenol (TGAP), 3,3′-diamino diphenyl sulfone (3,3′-DDS), and polyether sulfone (PES) composing the epoxy systems, respectively. The Polymer Consistent Force-Field (PCFF) 45 was used to describe the DGEBF, TGAP, 3,3′-DDS, and PES because the PCFF has been used to successfully describe a resin and curing agent in epoxy systems [33][34][35][36] . The total energies (E total s) of molecular structures of the epoxy systems were calculated using Eq.…”
Section: Simulation Methods and Model Preparationmentioning
confidence: 99%
“…Computational materials science techniques have been efficiently used to investigate the structural morphologies and diffusion properties of polymers in organic systems [26][27][28][29][30][31][32] . Other authors have recently investigated the mechanical properties of epoxy resin with curing agents [33][34][35][36][37] and the phase separation of epoxy systems [38][39][40][41] using computational materials science. Research into mechanical properties such as tensile and compressive stress-strain curves, Young's modulus, shear modulus, glass-transition temperature (T g ), and the phase separation of toughening agents with epoxy resin and curing agents is critical to achieving detailed atomic-level understanding of their behaviors.…”
mentioning
confidence: 99%
“…In particular, when employing the technique based on exploiting the structure or dynamics of entire polymer chains to estimate the interphase thickness, the value from about 2 to 3 Rg is usually obtained [42]. For the DGEBAepoxy resins, the value Rg ~ 12 -14 nm has been obtained [44].…”
Section: Resultsmentioning
confidence: 99%